Accelerated aqueous solubility and antibacterial activity of cefuroxime axetil using microcrystalline cellulose as carrier - Salam, Moushumi Tabassoom; Kumar, Ashim; Hata, Akito; Kondo, Hiromu; Salam, Md. Abdus; Wahed, Mir Imam Ibne; Khan, Md. Rafiqul Islam; Barman, Ranjan Kumar (Scientific Research Publishing, 2020)
This investigation was undertaken to enhance the solubility and consequent antibacterial activity of cefuroxime axetil (CA), a β-lactamase-stable broad spectrum second generation cephalosporin through solid dispersion (SD) technique. For this purpose, CA loaded SDs (CSDs) were prepared by solvent evaporation method using different concentrations of microcrystalline cellulose (MCC) as carrier. The CSDs were characterized by in-vitro dissolution study, thermal analysis (DSC), crystallinity (PXRD), interactions (FTIR) and morphology (SEM). Among the formulations, CSD-2 showed the highest dissolution rate which was 2.59-fold higher than pure CA with a drug-carrier (CA: MCC) ratio of 1:3. Enhanced dissolution rate was attributed to conversion of drug from crystalline to amorphous state during preparation of SDs, which was validated by DSC, PXRD, FTIR and SEM analyses. Antibacterial activity of CSD-2 against Staphylococcus aureus (ATCC 25923) and Escherichia coli (ATCC 25922) showed 1.94- and 6.75-fold higher relative zone of inhibition (RZOI), respectively than pure CA. CSD-2 has been found to be the most effective optimized formulation in terms of both enhanced dissolution rate and antibacterial activity. Thus, it can be an effective alternative to conventional dosage forms of CA. However, further investigations are needed to validate its pharmacokinetic properties, in-vivo antibacterial efficacy and safety before recommending as a novel formulation.